TSLP, IL‐31, IL‐33 and sST2 are new biomarkers in endophenotypic profiling of adult and childhood atopic dermatitis. (6th May 2016) - Nygaard, U.; Hvid, M.; Johansen, C.; Buchner, M.; Fölster‐Holst, R.; Deleuran, M.; Vestergaard, C.
Abstract: Background: Recent years have seen growing interest in identifying new biomarkers in atopic dermatitis (AD) that could serve as indicators of disease severity and predictors of treatment response. Objectives: We compared serum levels of thymic stromal lymphopoietin (TSLP), interleukin(IL)‐31, IL‐33 and soluble(s)ST2 in AD patients and healthy controls, investigated the possible correlation with disease severity, investigated if other atopic comorbidities could play a role, and assessed their potential as biomarkers in AD. Methods: Using standard enzyme‐linked immunosorbent assay techniques, we measured target serum levels in 71 adults and 61 children with AD, and 31 adult controls. We characterized our cohort by disease severity, radioallergosorbent test status concerning both dietary and inhalant allergens, and anamnestic reports of food allergy, concomitant allergic asthma and/or allergic rhinitis. Results: Serum levels of TSLP, IL‐31 and IL‐33, but not sST2, were significantly elevated in AD patients compared with controls. In AD patients, both IL‐31 and IL‐33 serum levels were higher in children than in adults, while the opposite was the case for sST2. We observed no correlation between disease severity and any of the investigated targets. While serum TSLP levels were unaffected by concomitant allergies and atopic comorbidities, serum levels of IL‐31, IL‐33 and sST2 were affected to a small extent. We found a positive correlation between TSLP, IL‐31 and IL‐33, and an inverse relationship between IL‐33 and sST2. Conclusions: The studied targets hold little potential as indicators of disease severity. The serum values of our targets show robustness against atopic comorbidities, allergies and changes in disease severity. This robustness strengthens their potential use in biomarker‐based stratification and could be instrumental in identifying subgroups and predicting the possible benefit of therapeutic and prevention approaches.